"Trying to Fit In": Multiethnic Parties, Ethno-Clientelism, and Power-Sharing in Bosnia and Herzegovina and Macedonia. Issue 3 (3rd July 2019) - Piacentini, Arianna
Abstract: Where do multi-ethnic parties fit in ethnically polarized multi-party systems? Can they effectively represent non-ethnicized communities in contexts that are deeply fragmented along ethnonational lines? How might they do so? This article analyzes the extent to which political parties attempting to build cross-ethnic support may succeed in representing non-ethnic communities. It does so by focusing on the ethnopolitical realities of two deeply divided societies, Bosnia and Herzegovina and North Macedonia. The article first explores the two countries' institutional and political functioning; it then assesses the many obstacles facing multi-ethnic parties as they attempt to cultivate cross-ethnic support. The findings demonstrate that, in addition to the "ethnicized" nature of political institutions, another major obstacle in representing citizens beyond the ethnic divide is the consolidation of ethno-clientelistic alliances, which prop up ethnicized masses' economic protection.